2003
DOI: 10.1287/orsc.14.5.497.16761
|View full text |Cite
|
Sign up to set email alerts
|

Learning About Failure: Bankruptcy, Firm Age, and the Resource-Based View

Abstract: Systematic differences in the determinants of firm failure between firms that fail early in their life and those that fail after having successfully negotiated the early liabilities of newness and adolescence are identified. Analysis of data from 339 Canadian corporate bankruptcies suggests that failure among younger firms may be attributable to deficiencies in managerial knowledge and financial management abilities. Failure among older firms, on the other hand, may be attributable to an inability to adapt to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
378
1
24

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 555 publications
(425 citation statements)
references
References 61 publications
(36 reference statements)
22
378
1
24
Order By: Relevance
“…Research has identified a diversity in types of exits: (1) voluntary exits to acquire a better job (Van Praag 2003;Bates 2005), (2) exits due to personal circumstances, (3) exits by way of successfully selling the firm (Headd 2003), and (4) bankruptcy (Thornhill and Amit 2003). It is likely that the type of exit and also the timing of exit -either in the "valley of death" (within 3 years after start-up) or later on -affect the entrepreneurial preferences subsequent to firm exit.…”
Section: Firm Exit Typementioning
confidence: 99%
“…Research has identified a diversity in types of exits: (1) voluntary exits to acquire a better job (Van Praag 2003;Bates 2005), (2) exits due to personal circumstances, (3) exits by way of successfully selling the firm (Headd 2003), and (4) bankruptcy (Thornhill and Amit 2003). It is likely that the type of exit and also the timing of exit -either in the "valley of death" (within 3 years after start-up) or later on -affect the entrepreneurial preferences subsequent to firm exit.…”
Section: Firm Exit Typementioning
confidence: 99%
“…This is likely to help to develop new theory rather than simply apply existing theory. For instance, finding new ways of using the resource based view (RBV) in the study of decline (Thornhill & Amit, 2003) could provide a better understanding of strategic resources, how they are obtained and, more importantly, how they are exhausted. For example, Norman, Butler and Ranft (2013) studied the influence of downsizing on resources.…”
Section: Challenges To Overcome When Conducting Research On Decline Amentioning
confidence: 99%
“…Competences and capabilities have not had the sufficient time to develop in order to provide competitive advantage. These include the lack of management competences (Thornhill and Amit 2003). Young organizations are constrained due to their inability to influence the external environment and their lack of legitimacy.…”
Section: Hypothesis 1a the Greater The Connectedness Of A Bank's Cusmentioning
confidence: 99%
“…Older organizations in contrast have had the opportunity to establish their reputation, credibility, reliability and accountability, but structural inertia may create an unreachable gap between the organization and its competitive environment leading to failure (Hannan andFreeman 1989, Thornhill andAmit 2003).…”
Section: Hypothesis 1a the Greater The Connectedness Of A Bank's Cusmentioning
confidence: 99%
See 1 more Smart Citation